The effects of the strategic management’s social responsibility of Iraqi public industrial companies on customers commitment. A Case Study on Samarra Pharmaceutical Company Co. - Ali, Shireen Nori Azeez (Technium Social Sciences Journal, 2021)
This paper examines the effects of the social responsibility of the strategic management of the Iraqi public industrial companies on the commitment of the customers. In this paper, a descriptive analytical approach was followed and three questionnaires were designed. It consists of (420) employees. The results concluded that there is a statistically significant correlation between the social responsibility of strategic management in Iraqi public companies and the commitment of customers; and those companies contribute through the strategies they adopt in attracting customers. Key words: strategy, management, social responsibility, Sustainability